Search for the lepton flavour violating decay τ- → μ-μ+μ- - Aaij, Roel; Adeva, B.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Journal of high energy physics, 2015)
A search for the lepton flavour violating decay τ− → μ−μ+μ− is performed with the LHCb experiment. The data sample corresponds to an integrated luminosity of 1.0 fb−1 of proton-proton collisions at a centre-of-mass energy of 7 TeV and 2.0 fb−1 at 8 TeV. No evidence is found for a signal, and a limit is set at 90% confidence level on the branching fraction, B(τ− → µ−µ+µ−) < 4.6 × 10−8.